Necesidades emocionales en cuidadores principales de pacientes con cáncer de estómago (2020)
Cancer is a disease that generates a great impact at a physical and phycological level, according to the World Health Organization (WHO), this chronic disease is the second cause of death in the world and its symptoms are usually evident when disease is at an advanced stage. Its impact does not only cause discomfort to the diagnosed patient, but also to his family and closest loved ones. The main caregiver is someone who is generally greatly involved, and is in charge of meeting all the patient’s demands, developing great physical and emotional dependency. Thus, the object of the present research is to describe the emotional needs of the main caregiver of a patient with stomach cancer; based on the theoretical concepts of the psycho-oncology. With a focus on cognitive – behaviorism, this qualitative study has a descriptive scope and uses depth interview as a technique for collecting data. The main emotional needs found are negative perceptions towards the disease and its ailment, fluctuations in mood, emotional overload, physical demands where modification of ties are found, internal and external changes; and external support requirements.